2023
DOI: 10.1002/cae.22664
|View full text |Cite
|
Sign up to set email alerts
|

The effects of educational robotics in programming education on students' programming success, computational thinking, and transfer of learning

Abstract: The study aims to investigate the effects of educational robotics (ER) in programming education on students' programming success, computational thinking (CT), and transfer of learning and to reveal the students' views about robotics programming. For this purpose, an explanatory sequential mixed‐method research design was used. In this research design, a qualitative data collection process follows a quantitative one to be able to further explain the novel results obtained through analysis of the quantitative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Upon examining the existing literature on the subject, it is evident that there is a higher prevalence of studies indicating a significant relationship between computational thinking and block coding (Atmatzidou & Demetriadis, 2016;Oluk, Korkmaz & Oluk, 2018;Totan & Korucu, 2023). On the other hand, certain studies exhibit congruity with the results of this study and no significant relationship can be found (Atman Uslu, Mumcu & Eğin, 2018;Yolcu, 2018). Webb Rosson (2013 points out that some of the reasons for not finding a significant relationship between computational thinking and coding in studies are the scarcity of resources used in the evaluation of computational thinking skills and the inability to measure different sub-skills.…”
Section: Results On Computational Thinking Skillsmentioning
confidence: 62%
“…Upon examining the existing literature on the subject, it is evident that there is a higher prevalence of studies indicating a significant relationship between computational thinking and block coding (Atmatzidou & Demetriadis, 2016;Oluk, Korkmaz & Oluk, 2018;Totan & Korucu, 2023). On the other hand, certain studies exhibit congruity with the results of this study and no significant relationship can be found (Atman Uslu, Mumcu & Eğin, 2018;Yolcu, 2018). Webb Rosson (2013 points out that some of the reasons for not finding a significant relationship between computational thinking and coding in studies are the scarcity of resources used in the evaluation of computational thinking skills and the inability to measure different sub-skills.…”
Section: Results On Computational Thinking Skillsmentioning
confidence: 62%
“…Based on the conducted theoretical research, the following mathematical skills were synthesized, which can be divided into two categories (Table 1). Some modern researches are aimed at establishing and confirming the benefits of using a robot in programming education [21], [35]. The main considered advantages are increasing the efficiency in learning concepts in computer science, computational thinking and motivation of learners.…”
Section: Defining Mathematical Competencies For the Objective Of The ...mentioning
confidence: 99%